Analysis of Agricultural Land Area Decrease on Income Inequality in East Java, Indonesia - Aqiilah, Hana Shifwatun; Sujarwo, Sujarwo; Toiba, Hery (Agro Bali : Agricultural Journal, 2025)
Income inequality remains a significant issue in developing nations, including East Java, which was ranked fifth among regions in Indonesia for having the highest level of inequality in 2023. This inequality is often associated with structural changes, especially the decrease of agricultural land to accommodate industrial development. This study aims to determine the most suitable spatial model, analyze the relationship between agricultural land reduction and income inequality in East Java, and explore the effects of other factors such as Agricultural Sector GDP, HDI, labor force, and real per capita expenditure on income inequality. The research uses secondary data, including panel data from 38 regencies/cities in East Java from 2009 to 2018. The results indicate spatial dependency among the independent variables, making the Spatial Autoregressive Model (SAR) the most appropriate method for analysis. These findings suggest that a significant decrease in agricultural land area tends to exacerbate income inequality even further. Therefore, this study has important policy implications, including the need for the government to uphold laws related to the protection of sustainable agricultural land and to provide skills training that is relevant to the needs of modern sectors. The results also show that an increase in the agricultural sector's GDP and labor force can boost productivity, output, and income, thereby potentially reducing income inequality. Whereas a rise in HDI and per capita expenditure tends to increase income inequality due to unequal access to development benefits and the consumption patterns of high-income groups, which further widen the gap.